2021
DOI: 10.3390/cryst11121452
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Fabrication Process of Gold Microdisk Arrays by the Direct Imprinting Method Using a PET Film Mold

Abstract: In this study, an efficient nanofabrication process of metal microdisk arrays using direct imprinting was developed. This process was comprised of three steps; sputter etching on the quartz glass substrate, gold thin film deposition on an etched surface of a substrate, and transfer imprinting using a polyethylene terephthalate (PET) film mold on the Au thin film. A new idea to utilize a PET film mold for disk patterning by the nano transfer imprinting was examined. The PET film mold was prepared by thermally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It was also revealed that the good uniformity of micro-ring structures led to higher improvement, while an exposed gold layer caused a reduction in the height and an expansion of the spectral absorbance. It is conceivable that the enhanced spectral absorbance can be controlled by the gold micro-ring structures on a quartz glass plate [23,24]. The optical characteristics of the gold layer on a glass plate were assessed via extinction spectrum.…”
Section: The Spectral Absorbance Propertiesmentioning
confidence: 99%
“…It was also revealed that the good uniformity of micro-ring structures led to higher improvement, while an exposed gold layer caused a reduction in the height and an expansion of the spectral absorbance. It is conceivable that the enhanced spectral absorbance can be controlled by the gold micro-ring structures on a quartz glass plate [23,24]. The optical characteristics of the gold layer on a glass plate were assessed via extinction spectrum.…”
Section: The Spectral Absorbance Propertiesmentioning
confidence: 99%
“…This technique, while innovative, has prompted further investigation into its scalability and application in the real world. Furthermore, the fabrication of metallic nanodot arrays has been explored using the nanochemical stamping technique with a polymer stamp [ 35 , 36 ]. This approach offers a high degree of precision and repeatability, making it suitable for applications in nanoelectronics and photonics.…”
Section: Introductionmentioning
confidence: 99%